Ai Weiwei "Law of the Journey" in the Time of Instagram. Issue 2 (1st December 2019) - Nguyen, James
Abstract : I first encountered Ai Weiwei's Law of the Journey as an amalgam of Instagram tiles (see photos on following page). The imposing sixty-meter-long rubber lifeboat—filled with faceless rubber bodies—was reduced to a scrollable algorithm. Posted across multiple time zones and geotagged in places like the Prague National Gallery to the most recent incarnation on Cockatoo Island (a decommissioned shipyard on Sydney harbor), Law of the Journey enjoyed much better travel rights and Visa entitlements than the actual refugees it depicted. While beyond the control of the artist or exhibiting venues, the mobility of images of Law of the Journey nonetheless made me think about the representations of refugees and border violence within the global art circuit.